Giant lipoma removal by Kshara Sutra thread in an outpatient department without stitches or antibiotics: a case report - Bapat, Prasad; Bapat, Vaidehi; Phalgune, Deepak (International Surgery Journal, 2022)
Surgical treatment of lipomas is considered when they are painful or unsightly. Surgical management can sometimes be tricky, and surgeons must keep in mind the potential risk of malignancy with large tumours. The present case was of a 46-year-old male with a giant lipoma with a neck on right buttock. Kshara Sutra thread ligation was performed in an outpatient department under local anaesthesia. No internal medication was given for wound healing or infection control. No stitches were taken. The lipoma was cut and removed on the third day without any post-operative complications such as infection, severe pain, or bleeding. Kshar Sutra treatment can be a safe, alternative herbal treatment for lipoma with the neck.